CRISPR Cas-9 genome editing and Islam: A religious perspective (Bangladesh Journal of Medical Science, 2018)
Background: Certainly, the ultimate aim of Islamic law is to “protect human life” either through mitigation of hardship or recognition of public interests reckons biomedical innovations allowable where-if cling by ethical, moral and legal principles. Assertively, if–CRISPR Cas- 9 genome editing–methods based on the guided principles of Islamic law and jurisprudence, as “harm has to be redressed” can be justified keeping in view the human dignity, honor and prestige. Hence, newer technologies can be adopted because “necessity renders prohibited things as permissible” with certain caveats. Arguably those who consider it as an evil must think over that “in the presence of two evils, the one whose injury is greater is avoided by the commission of the lesser”.Conclusion: Therefore if Cas-9 based method leaning towards evils, even then it can be acceptable in case where an atypical germ-line sequence can affect the next generation, which is indeed a great evil, and “the lesser of evils is preferred over the greater one” renders it permissible with a view it might enhance human health and living standard. Conversely, curing a minor disease if causing another equal infirmity or greater should be rendered forbidden as “harm cannot be removed by harm”, then, “a greater harm can be removed by a lesser one” germ-line editing/alteration in severe cases will be allowed on the basis of necessity.Bangladesh Journal of Medical Science Vol.18(1) 2019 p.7-13